On the Stability of Semilinear Nonautonomous Evolution Equations in Banach Spaces and Its Application to Strongly Parabolic Equations - Nguyen, Manh Hung; Tran, Thi Loan (Ukrains’kyi Matematychnyi Zhurnal, 2002)
The paper is concerned with the exponential stability of the zero solution of strongly nonautonomous parabolic equations. Conditions are found on time-dependent coefficients of a parabolic equation under which its solutions converge exponentially to 0 as t → ∞.